TRANSFORMATION OF US PRIORITIES IN BILATERAL RELATIONS WITH COUNTRIES OF THE MIDDLE EAST IN THE CONTEXT OF GLOBAL AND REGIONAL INTERNATIONAL POLITICAL SITUATION (Вісник: Міжнародні відносини, 2024)
The main stages and directions of transformation of the US priority system in bilateral relations with Middle Eastern countries are determined through their retrospective and prognostic analysis in the context of regional and global international political situation. The influence of American electoral processes on the transformation of US Middle East policy strategies is clarified. The mechanisms for implementing strategies such as "reduction," "non-intervention," "distant balancing," "containment and engagement," "regime change," "engagement as integration," "engagement as bargaining," "reconciliation," "maximum pressure," "containment and involvement" in bilateral relations with Middle Eastern countries are disclosed, along with the dynamics of American-Iranian and American-Saudi relations due to the application of selected strategies. It is proven that the influence of the US as a global power capable of exercising monopolistic control over the development of events and processes both at the global and regional (Middle Eastern) levels is diminishing, reflecting a broader shift in the global balance of power. The weakening of their leadership positions is particularly evident in the Middle East region, dominance in which was one of the guarantors of US global leadership. It is substantiated that most directions of US bilateral Middle Eastern policy have experienced negative dynamics due to the influence of both global and regional factors, including the strengthening of the positions of the PRC and the RF and intra-regional changes. If during the period of bipolar confrontation, global factors were key in shaping the priority system of US bilateral relations with Middle Eastern countries, then at the present stage, the role of regional factors is increasing while maintaining the importance of global ones (the need to counteract the PRC and the RF, the Russian-Ukrainian war, the Israel-Hamas conflict, the Iran-Israel confrontation).
Keywords: USA, Middle East, Persian Gulf, Islamic Republic of Iran (IRI), Kingdom of Saudi Arabia (KSA), Israel, Egypt, regional security, oil factor, D. Trump, J. Biden.